(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The labor market in the trend of international integration places requirements on the human resources of each organization, they need to be good at both expertise and use foreign languages fluently. This is also a factor that affects the training activities of each university in each country, especially in a developing country like Vietnam. This study analyzes the content related to the training activities of the university, which is determined by the author, which is the foreign language ability of students, including Input foreign language ability of students; and foreign language learning ability of students. These are the two contents that influence the output standards of university students, as mentioned by many studies. The author builds a research theoretical framework with the above contents and surveys 400 final students (course 2018-2022) of the university representing the block of social sciences of Vietnam - University of Social Sciences and Humanities, to assess the practice of students’ foreign language ability according to the prescribed output standards; evaluate the impact of the factor “student’s input foreign language ability” and the factor “student’s foreign language learning ability” on “output standards of student’s foreign language ability”. The survey results show that students’ "student’s input foreign language ability” is assessed at a lower level, which is a factor that has a great impact on the quality of training and affects the foreign language ability of students according to the output standards (output standards of student’s foreign language ability). From the results of this survey, the author makes research conclusions and discusses relevant issues to develop foreign language competence for students at the University of Social Sciences and Humanities and many universities in the region of Vietnamese social sciences.